Dinamika Populasi Bakteri Pada Budidaya Ikan Koi (Cyprinus rubrofuscus) Sistem Resirkulasi - Mahariawan, I Made Dedi; Andayani, Sri; Suprastyani, Heny; Sa’adati, Feni Tri (Jurnal Sumberdaya Akuatik Indopasifik, 2024)
Koi fish (Cyprinus rubrofuscus) is one of the aquaculture commodities that is highly marketable because of its unique color pattern and body shape. The prevalence of parasites and pathogenic agents in Koi fish among farmers poses challenges and leads to the occurrence of numerous illnesses. Water quality management is implemented in an effort to prevent several infectious microorganisms. The application of a recirculation system is used to enhance water quality and bolster the disease resistance of Koi fish. The objective of this study was to evaluate the application of RAS technology in the koi fish culture under different filter media on bacterial density. This study used four treatments, namely treatment A (RAS with a dacron filter and pumice), B (RAS with a dacron filter and sand), C (RAS with a sand and pumice filter), and K (control without a recirculation system). The parameter observed in this study was the density of bacteria in the koi fish rearing-media. These findings demonstrated that the utilization of various filters had an impact on bacterial density. Treatment C (RAS with sand and pumice filter) exhibited the greatest bacterial density with an average value exceeding 3.4 log CFU. mL-1 from the first week to the third week. The density of nitrifying bacteria in the koi fish production system is positively influenced by the high-quality maintenance practices that are maintained under optimal conditions.